The Historical Development And Challenges Of Islam In Shàré, Ifelodun Local Government, Kwara State, Nigeria - Gambari, Yusuph Dauda (MAQOLAT: Journal of Islamic Studies, 2023)
Shàré is an ancient Igbomina town in Kwara State, Nigeria. The town, which Muslims populate, features many Islamic practices. This makes it different from other communities in Igbominaland. Right from the second Olupako (king), the traditional heads of the town adorned themselves in turban instead of crowns as common to Yoruba Obas. This indicates their attachment to Islam. Some of the traditions of the community are embedded in Islamic values and practices. For instance, the popular December and New Year celebrations, held in high esteem in different towns, cities and villages, are nothing to write home about in Shàré. What is celebrated in the town by all and sundry is CĪdu ’l-Adhā. This paper considered it necessary to investigate the factors responsible for the wide acceptance of Islam in the town to determine what is needed to sustain the tempo in the future. The historical method is adopted to collate relevant materials critical to achieving this paper's objectives. The findings revealed that Islam got to Shàré during the reign of the second Olupako, who accepted the religion. This prepared the ground for drastic Islamic developments in the town. It is also discovered that until now, Muslims are still proactive in sustaining the influence of Islam. However, several challenges need attention to secure Islam's future in the community. Attentions are therefore called to those challenges in this paper for necessary measures to address them.